Answer:
Step-by-step explanation:
a) Pythagorean theorem,
altitude² + base² = hypotenuse²
h² + (w² - 1)² = (w² + 1)²
h² = (w² + 1)² - (w² - 1)²
{Compare with (a + b)² - (a -b)² = 4ab where a =w² & b = 1}
h² = 4*w²*1
h² = 4w²
![h=\sqrt{4w^{2}} = \sqrt{2*2*w*w} \\\\\\h = 2w](https://tex.z-dn.net/?f=h%3D%5Csqrt%7B4w%5E%7B2%7D%7D%20%3D%20%5Csqrt%7B2%2A2%2Aw%2Aw%7D%20%5C%5C%5C%5C%5C%5Ch%20%3D%202w)
b) Area of triangle = ![\frac{1}{2}b*h](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7Db%2Ah)
![=\dfrac{1}{2}*(w^{2}-1) *2w\\\\= (w^{2}-1)*w = w^{2}*w - 1*w\\\\=w^{3}-w](https://tex.z-dn.net/?f=%3D%5Cdfrac%7B1%7D%7B2%7D%2A%28w%5E%7B2%7D-1%29%20%2A2w%5C%5C%5C%5C%3D%20%28w%5E%7B2%7D-1%29%2Aw%20%3D%20w%5E%7B2%7D%2Aw%20-%201%2Aw%5C%5C%5C%5C%3Dw%5E%7B3%7D-w)
c) w =2
Area of triangle = 3w = 3*2 = 6
Answer:
x=2
Step-by-step explanation:
2x=4
x=4/2
x=2
Answer: X= -5
Step-by-step explanation:
I believe that the equation has X to the 2 power meaning that the answer for X is...
X= 10, and -10
The answer is zero hope that helps